Accumulation of Gastrodin, p-Hydroxybenzyl Alcohol, and Parishin in Gastrodia elata During Growth - Mingzheng Duan; Liuyuan Bao; Li Dong; Haiyan He; Lijun Cheng; Zhilong Shi; Honggao Liu; Shunqiang Yang (Journal of Food Quality)
Gastrodin (GA), p-hydroxybenzyl alcohol (PHA), and parishin (PAR; parishins A, B, C, and E, i.e., PA, PB, PC, and PE, respectively) are the main active components of the herbal plant Gastrodia elata Blume used for various medicinal purposes. Understanding the accumulation of these components during the growth of G. elata will provide a scientific basis for its harvesting. The present study utilized high-performance liquid chromatography (HPLC) to track the changes in the metabolic content in three tissues [seed stem (SS), connecting stem (ST; tissue from the SS to a new tuber [NB]), and NB] over 6 months (May, June, July, August, September, and December) during the growth of G. elata. This approach showed that the GA content increased gradually in both SS and ST, with the highest content (73.87 μg/g) observed in NB in December. The PHA content decreased initially in SS and then fluctuated in both SS and NB over time. The PAR content gradually decreased in SS (2460.61–576.18 μg/g in May to December), increased (2279.25 μg/g in August) initially in ST before decreasing (602.4 μg/g in June), and progressively increased in NB over time (495.39–2352.11 μg/g in June to December). Further analysis showed that GA was highly enriched in SS in all months, and the accumulated PA in June and July positively influenced the cumulative production of GA after June. The accumulation trend observed in the GA content in each tissue was opposite to that observed for the PAR content, which suggests that PAR-like substances in SS may be an important source of GA in NB. Thus, the present study’s findings provide novel insights into the accumulation of GA and PHA in G. elata during growth.